The importance of promotion towards visitor’s intention to visit event and festival / Nur Adelia Abu Bakar - Abu Bakar, Nur Adelia (2013)
Event and festival are the most important areas of the tourism industry. It contains the celebration of music, art, food, film or the uniqueness of the cultural that able to attract visitor. In order to make the visitor knows about the existing of the event and festival, promotion is needed so that the visitor is aware about the event and makes them have the intention to visit. For this study, the event and festival chosen is Tarian Cuti-cuti 1Malaysia Tourism Carnival. Most of the visitor that had visited the event knew about the event from society, association, word of mouth and not through the appropriate channel of promotion such as media. Thus, the visitor received insufficient information regarding the event. This study used convenience sampling and the sample size is; the visitor that visited the event and festival. The findings in this study revealed on the awareness factor; the relationship promotion and awareness factor that attract audience to visit event and festival; the relationship between awareness and intention to visit; and awareness as mediator towards the relationship between intention to visit and promotion. Meanwhile, the findings answered the objective and the hypotheses are accepted. The awareness as the mediator between promotion and intention to visit event or festival become the contribution of this study.